The impact of powerful programed exercises on fitness, on body composition - Beqa, Gentiana; Elezi, Abdullah; Elezi, Gresa (Journal of Education, Health and Sport, 2019)
The definition of body composition refers to the constituents of the tissues that make up the body and is usually used to indicate the relative percentage of body fat and non-fat tissue. The health interest is the recognition of the relative amount of body fat relative to non-fatty body tissue and the distribution of body fat, with additional interest in changes in these components under the influence of physical exercise. The purpose of this study is to validate the effects of a fitness program with strength exercises on female body composition. The population sampled for this research was defined as female populations Mean age = 23.28 years, SD = 2.18. The test sample consisted of 25 women who for the first time expressed a desire to practice at the “Gettfit Center” fitness center in Prishtina. The calculation of body composition parameters was done with the measuring instrument “TANITA” BC-601. Are calculated: Body Weight (BWEG), Body Fat (BOFA), Muscle Mass (MAMU), Bone Mass (BOMA), Body Mass Index (BMIN), Daily Caloric Intake (DCIN), Metabolic Age (MEAG), Body Water ( BWAT) and Visceral Fat (VIFA). Training sessions lasted 4 weeks with 1-12 workouts with 60% 1RM max loads, and 12 second 13 - 24 weeks training sessions with 80-85% 1RM loads, number of repetitions 8- 12. Quantitative analysis (Paired Sample T-Test) was applied to confirm the impact of the training treatment. The results show that exercise training for two months produced a significant positive effect at the level of p <0.0, in all parameters that determine body fat level and increase in muscle mass.